Hidradenocarcinoma of the Scrotum with Lymph Node Metastasis - Simões, Maria Inês (2018)
Hidradenocarcinoma is a rare neoplasm of the eccrine cells of the sweat glands, usually asymptomatic with slow growing and higher incidence between 50 and 80 years, occurring in both sexes and preferentially located in the palmar, plantar, frontal, axillary and nuchal regions. It has an aggressive behavior, with high rate of local recurrence and distance metastasis, associated with a poor prognosis. We present a case of hidradenocarcinoma of the scrotum manifested by lymph node metastasis through an exercise of clinical and histological differential diagnosis of an inguinal adenopathy in a young adult.